Creativity In Drawing For Alpha Generation Children To Enhance Creative Potential - Saskia Hanifaratri, Anindya; Eko Sugiarto; Syakir Syakir (Catharsis, 2025)
Generation Alpha, growing up in a digital environment, has unique characteristics in expressing creativity through visual arts. This research aims to explore how drawing creation can serve as an effective medium to enhance the creative potential of Generation Alpha children. The research method employed a mixed-method approach with 12 child participants from Sanggar Rumah Kreatifa 443 Semarang aged 6-11 years. Data were collected through participatory observation, in-depth interviews, and documentation of artworks, then analyzed using the Miles & Huberman interactive model. Results showed artwork visualization dominated by natural landscape themes (41.7%), digital characters (16.7%), and social activities (13.9%). Typological analysis revealed visual type dominance (50%) with Mini-C Creativity level appropriate to developmental stages, distributed in good (50%), moderate (41.7%), and fair (8.3%) categories. Unique characteristics of Generation Alpha manifested in the ability to integrate digital experiences with traditional media, openness to technology themes, and strong individual expression. Conducive learning environments with individual approaches and community support proved crucial in optimizing creative potential. Findings confirm that Generation Alpha creativity develops through systemic interactions between generational characteristics, individual typology, and responsive environmental support.